A Challenging Case of Pseudohyperkalemia in Chronic Lymphocytic Leukemia - Muhamad Alhaj Moustafa MD; Vera Malkovska MD; Sherif Elmahdy MD; Joseph Catlett MD (SAGE Publishing, 2017)
Pseudohyperkalemia is an uncommon finding in chronic lymphocytic leukemia. It is a misleading condition that could lead to iatrogenic hypokalemia when unwarranted treatment is administered. We describe an interesting case of pseudohyperkalemia in severe leukocytosis and how we identified it.